The use of acute nicotine treatment to ameliorate the ultrastructural changes of neuron in the hippocampus CA1 region due to REM sleep deprivation - Abd Rashid, Norlinda; H., Hapidin; A., Abdullah; Z., Ismail; Idris, Long (Universiti Putra Malaysia, 2018)
Rapid eye movement (REM) sleep deprivation is associated with learning and memory impairment accompanied by changes in the expression of the downstream regulatory antagonistic modulator (DREAM), cAMP response element-binding (CREB) and brain-derived neurotrophic factor (BDNF) proteins in the hippocampus. Acute nicotine treatment has been shown to attenuate this effect. This study was conducted to investigate the effects of acute nicotine treatment on changes of ultrastructural of neuron in the hippocampus CA1 region due to REM sleep deprivation. Sprague Dawley rats were subjected to a normal condition, REM sleep deprivation and control wide platform condition for 72 hours. During this procedure, saline or nicotine (1 mg/kg) was given subcutaneously twice a day. Then, the rats were sacrificed and the brain was harvested for Transmission Electron Microscopy (TEM) analysis. TEM analysis found that REM sleep deprivation for 72 hours significantly changes the ultrastructure of the neurons in the hippocampus CA1 region compared to the other groups. Treatment with acute nicotine significantly ameliorated these changes. This study suggests that acute nicotine treatment can prevent learning and memory impairment by ameliorating the ultrastructural changes in the neurons of the hippocampus CA1 region due to REM sleep deprivation